Seguridad de suministro: un valor en alza para la política energética y en la política de seguridad nacional - Quinto, Javier de (UNISCI Discussion Papers, 2007)
Energy security is nowadays one of the key world issues that affect the states’ economies and security policies . The international environment has changed and it will not be easy to forecast oil and gas prices. There is also another fundamental factor: the increasing greenhouse effect gas emissions from energy production and use. Finding the balance between security of supply, environmental impact and prices is the key for the future energy policy, linked to other objectives such as the strength of national companies or the coherence with other policies. The article proposes nine measures to facilitate Spain’s security of supply.